(untitled) (Al-Farooq Journal of Sciences, 2026)
Moroccan immigrants played a significant cultural role alongside their Egyptian counterparts in all academic institutions. This was particularly evident in their presence at Al-Azhar University, where they received their education. Moroccans considered Al-Azhar the university that shouldered the burden of education while also preserving Islamic heritage. This was further demonstrated through their presence in the kuttabs (traditional Quranic schools), one of the oldest educational institutions, and in other schools that were widespread in Cairo.